Differential accumulation of manganese in three mature tree species (Holoptelia, Cassia, Neem) growing on a mine dump - Raju, D.; Kumar, Sunil; Mehta, Urmil J.; Hazra, Sulekha (Current Science, 2008)
Three trees, including Cassia siamea (Cassia), Azadirachta indica (Neem), Holoptelia integrifolia (Holoptelia) belonging to three different families were identified from a manganese mine tailing dump. Manganese content in dump soil and in the stem, green leaves and dry, fallen leaves of the plants was determined. Values were compared with similar samples collected from normal vegetation. Under control condition, manganese content was highest in Cassia. Distribution of metal in samples collected from the dump site revealed that Holoptelia has a special ability to accumulate high amounts of manganese under stress condition followed by Cassia and Neem. There is no literature on metal accumulation in Holoptelia. Mechanism of manganese sequestration in Holoptelia is different from the other two trees growing in the same soil.
Keywords: Azadirachta indica; Cassia siamea; Holoptelia integrifolia; hyperaccumulator; manganese; mine dump

Mixed Co-Mn oxide-catalysed selective aerobic oxidation of vanillyl alcohol to vanillin in base-free conditions - Jha, Ajay; Patil, Kashinath R.; Rode, Chandrashekhar V. (Chempluschem, 2013)
Manganese-doped cobalt mixed oxide (MnCo-MO) catalyst was prepared by a solvothermal method. The as-prepared catalyst was characterised by X-ray photoelectron spectroscopy, H-2 temperature-programmed reduction, O-2 temperature-programmed oxidation and XRD. This catalyst gave 62% conversion with 83% selectivity to vanillin in 2hours for the liquid-phase air oxidation of vanillyl alcohol without using base. Three different types of metal oxides were observed in the prepared catalyst, which could be identified as Co3O4, Mn3O4 and CoMn2O4. Among these, the tetragonal phase of CoMn2O4 was found to be more active and selective for vanillyl alcohol oxidation than Co3O4 and Mn3O4. High-resolution TEM characterisation revealed the morphology of MnCo-MO nanorods with a particle size of 10nm. Successful recycling of the catalyst was also established in this oxidation reaction.
Keywords: aerobic oxidation; cobalt; heterogeneous catalysis; manganese; spinel phases

Manganese increases high mannose glycoform on monoclonal antibody expressed in cho when glucose is absent or limiting: implications for use of alternate sugars - Surve, Tanaya; Gadgil, Mugdha (Biotechnology Progress, 2015)
Alternate sugars such as galactose and fructose are metabolized at a slower rate than glucose and result in lower accumulation of lactate. While low lactate accumulation is desirable, we report that complete substitution of glucose with these sugars results in an increase in M5 high mannose glycans. Surprisingly, this increase is much higher when the culture is supplemented with manganese: for example, when cells are cultured with galactose, M5 high mannose glycan content increased from 5% at 1 nM Mn2+ in the basal medium to 32% with 16 mu M Mn2+ supplementation. When galactose is supplemented with glucose maintained at low concentrations, a small reduction in high mannose glycans is seen. In control cultures with glucose, the high mannose content was however <2% in this range of Mn2+ concentration. By varying Mn2+ and glucose supplementation levels, with or without galactose, we systematically demonstrate that Mn2+ concentration and glucose availability, together, significantly affect the high mannose glycan content. To our knowledge, this is the first report that shows that the effect of Mn2+ on high mannose glycan content depends on glucose availability. At each Mn2+ supplementation level evaluated, galactosylation percentages were highest for cultures where galactose was supplemented with glucose at non-limiting concentration. (c) 2014 American Institute of Chemical Engineers Biotechnol. Prog., 31:460-467, 2015
Keywords: CHO; fructose; galactose; glucose; glycosylation; high-mannose glycan; manganese

Manganese incorporated on glucose as an efficient catalyst for the synthesis of adipic acid using molecular O2 in aqueous medium - Nale, S.D. (Applied Catalysis A: General, 2017)
A new manganese incorporated on glucose catalyst Mn@CC-SO3H-NH2 was synthesized and well characterized using FT-IR, PXRD, EDAX, SEM, TEM, [13] C cross-polarization NMR and BET analysis. The catalyst thus synthesized was studied for its utility in the synthesis of industrially important chemical adipic acid starting from readily available cyclohexanone using molecular O2 as a source. Adipic acid was obtained in maximum yield of 82% using Mn@CC-SO3H-NH2 catalyst in water as a solvent. The catalyst was easily recovered and reused for minimum five runs without any significant loss in the yield of products. Using molecular O2 as an oxidant and water as a solvent, the reaction is very important from green chemistry perspectives and can also be industrially feasible.
Keywords: Adipic Acid; Catalyst; manganese; recyclable; Water

Zinc supplementation decreases galactosylation of recombinant IgG in CHO cells - Prabhu, Anuja (Applied Microbiology and Biotechnology, 2018)
Trace element composition of culture medium can be altered to modulate glycoform of recombinant glycoproteins. In this study, we show that Zn2+ supplementation at or above 100 μM decreases galactosylation of recombinant IgG expressed in Chinese Hamster Ovary cells. This decrease in galactosylation is not due to reduced galactosyltransferase expression. This effect persists upon supplementation of galactose and uridine to the culture, indicating that it may not be due to reduced UDP-Gal availability. Measurements of galactosyltransferase activity in the cell lysate show that activity decreases with increasing Zn2+/Mn2+ ratio. This suggests that one possible explanation of the effect of Zn2+ may be reduced intracellular galactosyltransferase activity due to increase in Zn2+/Mn2+ ratio. Consistent with this, the decrease in galactosylation of IgG could be reversed by supplementation of Mn2+ (a cofactor of galactosyltransferase) which increases intracellular Mn2+ content. Measurement of total intracellular Zn2+ content, however, indicates no significant upregulation of total intracellular Zn2+ content and no significant downregulation of intracellular Mn2+ content with Zn2+ supplementation. One possible explanation could be that cellular detoxification response to higher extracellular Zn2+ concentration might lead to changes in intracellular distribution of Mn2+. In this case, Zn2+ supplementation would be expected to interfere with other known effects of Mn2+. Indeed, the previously reported increase in high mannose glycans upon Mn2+ supplementation in the absence of glucose is reversed by Zn2+ supplementation. This study also suggests the use of Mn2+ supplementation as a strategy to overcome the effect of lot-to-lot variability in trace element concentrations on galactosylation.
Keywords: CHO cells; glycosylation; manganese; Trace metals; zinc

Manganese-catalyzed alpha-olefination of nitriles with secondary alcohols - Yadav, Vinita; Landge, Vinod G.; Subaramanian, Murugan; Balaraman, Ekambaram (ACS Catalysis, 2020)
An expedient catalytic approach for alpha-olefination of nitriles using secondary alcohols with the liberation of molecular hydrogen and water as the only byproducts is reported. This reaction is catalyzed by a molecularly defined manganese(I) pincer complex and operates in the absence of any hydrogen acceptors. A broad range of substrates including cyclic, acyclic, and benzylic alcohols, as well as various nitrile derivatives, such as arylmethyl and heteroarylmethyl nitriles, are employed in the reaction to provide a diverse range of alpha-vinyl nitriles in good to excellent yields. Mechanistic studies showed that the reaction proceeds via dehydrogenative pathway and the activation of alpha(C-H) bond of the alcohol is the rate-determining step.
Keywords: acceptorless dehydrogenation; Alcohol; alpha-olefination; Hydrogen; manganese

Phosphine-free manganese(II)-catalyst enables acceptorless dehydrogenative coupling of alcohols with indoles - Yadav, Vinita; Balaraman, Ekambaram; Mhaske, Santosh B. (Advanced Synthesis & Catalysis, 2021)
Herein, an air-stable, molecularly defined NNN-Mn(II) pincer complex catalyzed acceptorless dehydrogenative coupling of alcohols with indoles is reported. A wide variety of symmetrical and unsymmetrical bis(indolyl)methane derivatives as well as some structurally important products such as Vibrindole A, Turbomycin B alkaloid, Antileukemic, and Anticancer agents were synthesized. Mechanistic studies illustrate the importance of the NH moiety in the complex and the crucial role of metal-ligand cooperation during catalysis.
Keywords: acceptorless dehydrogenation; Alcohol; Indole; manganese; phosphine-free

Manganese-catalyzed C(sp(2))-H alkylation of indolines and arenes with unactivated alkyl bromides - Verma, Suryadev K.; Punji, Benudhar (Chemistry-an Asian Journal, 2022)
Selective C(sp(2))-H bond alkylation of indoline, carbazole and (2-pyridinyl)arenes with unactivated alkyl bromides is achieved using MnBr2 catalyst in the absence of an external ligand. The alkylation uses a simple LiHMDS base and avoids the necessity of Grignard reagent, unlike other Mn-catalyzed C-H functionalization. This reaction proceeded either through a five- or a less-favored six-membered metallacycle, and tolerated diverse functionalities, including alkenyl, alkynyl, silyl, aryl ether, pyrrolyl, indolyl, carbazolyl and alkyl bearing fatty alcohol and polycyclic-steroid moieties. Alkylation follows a single electron transfer (SET) pathway involving 1e oxidative addition of alkyl bromide and a rate-limiting C-H metalation.
Keywords: Alkylation; C-H activation; indoline; ligand-free; manganese

Ligand-free MnBr2-catalyzed chemo- and stereoselective hydroboration of terminal alkynes - Pawar, Rameshwar B.; Karmur, Mital H.; Punji, Benudhar (Chemistry-an asian jounrnal, 2024)
Developing simple and benign protocols for synthesizing alkenylboronates is crucial as they are synthetically valuable compounds in various organic transformations. In this work, we report a straightforward ligand-free protocol for synthesizing alkenylboronates via atom-economical hydroboration of alkynes with HBpin catalyzed by a manganese salt. The reaction shows a high level of chemo and regioselectivity for the terminal alkynes and exclusively produces E-selective alkenylboronates. The hydroboration scope is vast, with the resilience of a range of synthetically beneficial functionalities, such as halides, ether, alkenyl, silyl and thiophenyl groups. This reaction proceeds through the involvement of a metal-hydride intermediate. The developed alkenylboronate can be smoothly converted to useful C-C, C-N and C-I bond-forming reactions.
Keywords: alkenylboronates; alkyne; Hydroboration; manganese; stereoselectivity

Manganese-catalyzed chemoselective direct hydrogenation of α,β-epoxy ketones and α-ketoamides at room temperature - Shabade, Anand B.; Singh, Rahul K.; Gonnade, Rajesh G.; Punji, Benudhar (Advanced Synthesis & Catalysis, 2024)
Chemoselective hydrogenation of alpha,beta-epoxy ketones and alpha-ketoamides is achieved at room temperature (25 degrees C) using 2.0 bar H-2 and a pincer-ligated Mn(I) catalyst that provides synthetically valuable alpha-hydroxy epoxides and alpha-hydroxy amides. This protocol applies to a wide range of alkyl- and aryl-substituted alpha,beta-epoxy ketones, including terpenes (alpha-ionone, nootkatone, and R-carvone)- and steroids (testosterone and progesterone)-derived epoxy ketones, and tolerates H-2 sensitive functionalities, such as halides, acetyl, nitrile, nitro, epoxide, alkenyl and alkynyl groups. Additionally, alpha-ketoamides bearing reducible functional groups, including acetyl and diazo benzene, were untouched under this protocol and selectively converted to alpha-hydroxy amides. A preliminary mechanistic study highlighted the metal-ligand cooperative H-2 activation process.
Keywords: alpha; beta-epoxy ketones; chemoselectivity; direct hydrogenation; manganese; Metal-ligand cooperation